Swim performance in the improvement phase - Brito, C. A. F.; Pinto, R. F. (2002)
The purpose of this study was determine the performance of swim and the motor ability in the phase of perfectioning in function of the age, gender and some antropometric features. It was evaluat about 104 swimmers between 11 and 12 years old, that participated of regular swimming classes, twice a week, about 50 minutes in each session, in countryside of the state of São Paulo State. It was make antropometric evaluations (Guedes and Guedes, 1997) and performance (Brito and Pinto, 1999) specifics of swimming. The tests were carried out by four experienced teachers in two weeks. The descriptive analysis datas used independent "t".Student`s and it was adopt significance level p < 0,05. DISCUSSION The results are in line with literature in reference to antropometric behavior (Guedes and Guedes, 1997) and performance (Pelayo et all, 1997). But it is necessary to discuss a specific question: Could the biological results presented in the research, supported by physiology explanation, be responsible for the swimming performance? We believe it is interesting to consider these aspects involved in the swimming ability and mainly that these data could be used for future investigations by researchers, teachers and coaches who work in the area (Brito, 2000).